2022
DOI: 10.1002/asia.202200515
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical, Photophysical, Morphological and DFT Study of Polymorphic Sn(IV)‐Porphyrins Containing Fluorinated Axial Ligand

Abstract: In this study, we report the polymorphism of six coordinated Sn(IV)‐ tetrabromophenyl porphyrins axially armed with fluorine‐substituted phenolate ligands (structural formula [Sn(TBrPP)2+(A−)2], where A is the axial ligand=3,5‐difluoro phenol, compound 1). One form stabilizes in triclinic system (namely, 1α), and the other stabilizes in monoclinic system (namely, 1β). The two 1α and 1β polymorphs display distinct photophysical and morphological properties in the solid state. X‐ray diffraction study reveals tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The interaction of metalloporphyrins with donor molecules via axial coordination can strongly influence either the photophysical properties and the efficiency of energy or the electron transfer processes [8]. Over the last few decades, many crystalline structures of porphyrins or metalloporphyrins whose optical properties and crystal packing are governed by axial ligands coordination modes have been reported [9]. Among the M(II)-porphyrins, cobalt(II) porphyrins are the most studied compounds, since they are more sensitive to light irradiation and can change their oxidation state [10].…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of metalloporphyrins with donor molecules via axial coordination can strongly influence either the photophysical properties and the efficiency of energy or the electron transfer processes [8]. Over the last few decades, many crystalline structures of porphyrins or metalloporphyrins whose optical properties and crystal packing are governed by axial ligands coordination modes have been reported [9]. Among the M(II)-porphyrins, cobalt(II) porphyrins are the most studied compounds, since they are more sensitive to light irradiation and can change their oxidation state [10].…”
Section: Introductionmentioning
confidence: 99%
“…Row et al reported a database study which highlights the role of C-halogen···π interactions that aids the halogenated ligands to bind effectively to the target nucleic acids . Goldberg and his colleagues have documented numerous supramolecular structures using molecular building blocks derived from tetra­(iodophenyl) porphyrin (TIPP) and its derivatives. Patra et al demonstrated the influence of an axial linker toward the size of σ-holes on halogen atoms for hexacoordinated tin tetra­(iodophenyl) porphyrin scaffolds. , Nandi and Goldberg reported the occurrence of cooperative halogen bonding between the multi-porphyrin coordination assemblies …”
Section: Introductionmentioning
confidence: 99%
“…30−32 Patra et al demonstrated the influence of an axial linker toward the size of σ-holes on halogen atoms for hexacoordinated tin tetra(iodophenyl) porphyrin scaffolds. 33,34 Nandi and Goldberg reported the occurrence of cooperative halogen bonding between the multi-porphyrin coordination assemblies. 35 Spilfogel and colleagues conducted a database study of bromine-based halogen bonding interactions between porphyrins.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently we have also reported the effect of hetero-halogen interactions on crystal packing and solid-state properties like polymorphism. 21 Compounding difficulties in understanding the nature of X⋯X (hetero-halogen) interactions also arise due to a significant range in the electronegativity (F > Cl > Br > I) and polarizability (I > Br > Cl > F) of different halogens. [11][12][13] Thus, depending on the circumstances, a halogen acts as either an electropositive or an electronegative entity, or in some cases with no particular electrostatic character.…”
Section: Introductionmentioning
confidence: 99%